Research methods in teletandem context: approaches and possibilities - ARANHA, Solange; RAMPAZZO, Laura (The ESPecialist, 2022)
The purposes of this paper are to (i) show how research in teletandem has been carried out over the years since the beginning of the Project Teletandem Brasil: Foreign Languages for All; (ii) relate the context to the possibilities of data collection; (iii) discuss methodological approaches applicable to teletandem; (iv) introduce MulTeC (Multimodal Teletandem Corpus) as an alternative for diverse types of research. We empirically demonstrate data from theses, dissertations, and papers related to methodology; present approaches of methodological research from quantitative and qualitative perspectives, presenting characteristics of each; discuss how viable individual data collection is; demonstrate how MulTeC (Multimodal Teletandem Corpus) may help researchers and be used as a model for future data collection. Finally, we share some current research using the mentioned corpus in an attempt to show an array of possibilities both from the qualitative and quantitative perspectives.